Pengaruh Perceived Value dan Event Quality terhadap Revisit Intention dengan Satisfaction sebagai Variabel Mediasi: Studi pada Event Car Free Day - Puput Lestari; Yulyanti Fahruna; Ahmadi Ahmadi; Harry Setiawan; Wenny Pebrianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Car Free Day (CFD) has transformed into a strategic public space that not only encourages a healthy lifestyle but also becomes a massive socio-economic recreation arena. However, high visitor numbers do not guarantee the sustainability of the event, indicating challenges in managing the quality of the experience to build long-term loyalty. This study aims to analyze the influence of Event Quality and Perceived Value on the Revisit Intention of CFD visitors in Indonesia, with Satisfaction as a mediating variable. The research method uses a causal quantitative approach. Data were collected from 220 CFD visitors in various cities in Indonesia and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The theoretical contribution of this study strengthens the Stimulus-Organism-Response (SOR) paradigm by proving that the variables Perceived Value and Event Quality act as stimuli that significantly influence visitors' internal conditions (Satisfaction) to produce a behavioral response in the form of Revisit Intention. The practical contribution of this study provides input for CFD managers to prioritize improving the quality of event attributes and functional value to create sustainable visitor satisfaction. The results of this study indicate that satisfaction plays a central role in mediating the relationship between quality and value attributes and revisit intention.